A framework for economic evaluation of smallholder agroforestry: With particular reference to the semi-arid zone of West Africa - Williams, Timothy O. (Nitrogen Fixing Tree Association, 1992)
This paper presents a framework for economic analysis of smallholder agroforestry systems in the Sahel of West Africa. The approach developed makes use of the technique of investment analysis, but incorporates into it a framework that recognizes the special features of some agroforestry costs and benefits which may not be quantifiable in monetary terms. The main emphasis is to capture and utilize a wide range of information on costs, benefits, and indigenous practices than is encompassed by conventional valuation techniques. A hypothetical example is used to illustrate the approach and how various economic tools and concepts can be combined to help determine the profitability of an agroforestry system to both the individual farmer and the nation as a whole.